The importance of Rydberg orbitals in dissociative ionization of small hydrocarbon molecules in intense laser fields - Jochim, Bethany; Siemering, R.; Zohrabi, M.; Voznyuk, O.; Mahowald, J. B.; Schmitz, D. G.; Betsch, K. J.; Berry, Ben; Severt, T.; Kling, Nora G.; Burwitz, T. G.; Carnes, K. D.; et al. (My University, 2017)
Much of our intuition about strong-field processes is built upon studies of diatomic molecules, which typically have electronic states that are relatively well separated in energy. In polyatomic molecules, however, the electronic states are closer together, leading to more complex interactions. A combined experimental and theoretical investigation of strong-field ionization followed by hydrogen elimination in the hydrocarbon series C2D2, C2D4 and C2D6 reveals that the photofragment angular distributions can only be understood when the field-dressed orbitals rather than the field-free orbitals are considered. Our measured angular distributions and intensity dependence show that these field-dressed orbitals can have strong Rydberg character for certain orientations of the molecule relative to the laser polarization and that they may contribute significantly to the hydrogen elimination dissociative ionization yield. These findings suggest that Rydberg contributions to field-dressed orbitals should be routinely considered when studying polyatomic molecules in intense laser fields.